Milly, Molly and BiddyBid - Pittar, Gill; Morrell, Cris (Milly Molly Books Gisborne, N.Z., 2003)
Milly and Molly forgive BiddyBid when she yawns and wrongly accuses them of eating too many plums. Includes teaching guide. Suggested level: junior